EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS WEBSITE DALAM MENGEKSPLOR KEMAMPUAN NUMERASI MATEMATIS BERDASARKAN BEHAVIORISME PESERTA DIDIK - Ali, Nabila Nurhaliza; Supratman, Supratman; Rahayu, Diar Veni (UIN Imam Bonjol Padang, 2024)
Technology today continues to develop in various fields, including learning technology. One of the many learning methods that can improve the quality and quantity of learning is website-based learning. In the current era, many students access the website as an online learning resource. So the purpose of this study is to analyze the effectiveness of website-based learning media in exploring mathematical numeracy skills based on student behaviorism. This type of quantitative research with one group pretest-posttest design. Data collection techniques in the form of pre-test and post-test through questions of mathematical numeracy skills. The research was conducted at one of the State Junior High Schools in Ciamis Regency with the research subjects of class VII as many as 30 students who participated in the entire series of studies. The results of this study indicate that the web-based learning media developed based on learner behaviorism is effective in exploring mathematical numeracy skills, with the quality of effectiveness (effect size) of 1.47692 1.00 being in the